Fiscalização eletrônica da velocidade de veículos e redução de acidente de trânsito em Fortaleza - Ce - Lima, Dalba de Oliveira (2009)
Examines the importance of reducing the number of traffic accidents through the installation of Electronic Speed Reducers (ESR) in crossings in the city of Fortaleza. With the use of ever more advanced technology, the ESR's are present in many cities of the country to control the speed of car in places considered critical, recording the speed of car at a distance, the board, identifying violators. For this analysis uses the index of severity called Unit Standard Severity (UPS), a technology that identifies the critical locations from the severity of accidents, each involving a situation (with fatal victims, with wounded and material damage) a certain weight, prioritizing those accidents which result was more severe in terms of victims. Presents results obtained with the technique used.